Power Relations In ‘Spider-Man: Across The Spider-Verse’ Movie (2023): A Foucauldian Analysis - Zulkarnaen, Dicky Morgana; Jauwena, Gavriel Dylan; Brasco, Putra Pratama Immanuel; Steinlie, Granardo (Yayasan Pendidikan Gereja Masehi Advent Hari Ketujuh Makarios, 2024)
This study aims at unveiling the power issue found in the movie, “Spider-Man: Across The Spider-Verse,” a multi-layered story and profound symbolism. This study analyzed the movie’s thematic effects using a variety of literary theories and cinematic analysis. Furthermore, the study investigated how the film's nuanced use of images and visual themes enhanced the overall story and elicits emotional resonance in the spectator. Having the movie analyzed, the theory of Power, Discipline and Punish: The Birth of the Prison by Mitchel Foucault (1977), was used to criticize the power dynamic issue in the movie. As a result, 1) Leadership Conflict and Sovereign Power: The clash between Miles and Miguel highlights a conflict in ideals within the spider society. Miguel, as a leader, exerts sovereign power to control events, showcasing the dynamic of leadership struggles. 2) Resistance Against Anomaly and Exclusion: The designation of Miles as an